2018
DOI: 10.3126/jcmc.v8i1.23720
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of rectal prolapse in Chitwan Medical College

Abstract: Rectal prolapse (RP) is an unusual anorectal disease affecting both children and adults. Complete rectal prolapse represents full thickness protrusion of the rectum through the anal verge. Incarceration and strangulation are the most unusual, but dreaded complications of rectal prolapse that requires a surgical emergency. Management of such complications is still controversial. Some prefer conservative management by application of sugar while other preferred operative intervention. When prolapse is not reducib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…Furthermore, comparing the morbidity rates, there were similar rates in the study groups as well. The Delorme procedure remains a good surgical choice for patients with a mucosal or partial thickness rectal prolapse, and it is the best option for patients with only short full thickness rectal prolapsed [13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, comparing the morbidity rates, there were similar rates in the study groups as well. The Delorme procedure remains a good surgical choice for patients with a mucosal or partial thickness rectal prolapse, and it is the best option for patients with only short full thickness rectal prolapsed [13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…Assertiveness is considered a valuable nursing skill since it brings numerous benefits for nurses [5] . A quantitative research conducted on assertiveness training programs has shown significant impacts on improving assertiveness among nurses and nursing students worldwide [6] . In current health care environments, professional nurses need to become more aware about the use of assertive techniques in their workplaces to manage the challenges they face when dealing with human resources.…”
Section: Need For the Studymentioning
confidence: 99%